2020
DOI: 10.21203/rs.3.rs-111958/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

USP16 Regulates Castration-Resistant Prostate Cancer Cell Proliferation by Deubiquitinating and Stablizing c-Myc

Abstract: Backgroundc-Myc, a well-established oncogene, plays an important role in the initiation and progression of various cancers, including prostate cancer. However, its mechanism in cancer cell remains largely unknown and whether there exist a deubiquitinase targeting c-Myc also remains elusive.MethodsBioinformatic analysis and shRNA screening methods were used to identify potential deubiquitinases that correlate with c-Myc gene signature. Cell proliferation and viability were measured by Cell-Counting-Kit 8 and co… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…In the present study, it was found that CEM-C1 cells exhibited higher protein expression levels of c-Myc compared with those in CEM-C7 cells. Since c-Myc has been associated with drug resistance in various studies (24)(25)(26)(27), the present study aimed to reveal the anti-leukemic effect and reversal resistance effect of SAL, and to investigate c-Myc in T-ALL cells and its association with DEX resistance. CCK8 assay.…”
Section: Salidroside Overcomes Dexamethasone Resistance In T-acute Lymphoblastic Leukemia Cellsmentioning
confidence: 99%
“…In the present study, it was found that CEM-C1 cells exhibited higher protein expression levels of c-Myc compared with those in CEM-C7 cells. Since c-Myc has been associated with drug resistance in various studies (24)(25)(26)(27), the present study aimed to reveal the anti-leukemic effect and reversal resistance effect of SAL, and to investigate c-Myc in T-ALL cells and its association with DEX resistance. CCK8 assay.…”
Section: Salidroside Overcomes Dexamethasone Resistance In T-acute Lymphoblastic Leukemia Cellsmentioning
confidence: 99%